Legal Protection Efforts for Women Victims of Dating Violence by Gorontalo City Police Resort - Yusuf, Sakila Rahmania; Puluhulawa, Fenty U.; Mandjo, Julius T. (Universitas Negeri Gorontalo, 2024)
The purpose of this research is to find out how legal protection efforts against women victims of dating violence by the Gorontalo City Resort Police. The research method used in this research is empirical research method with qualitative approach. The result of this research is that the high number of violence is a concern for the wider community, especially the number of violence in dating relationships for unmarried women is quite alarming lately. The 2016 PPA symphony states that of the 10,847 perpetrators of violence, 2,090 perpetrators were boyfriends/friends. Dating violence is an act of violence against a partner who is not yet married, including physical, emotional, economic violence and activity restrictions. This violence is a case that often occurs after domestic violence, but still does not get the spotlight compared to domestic violence, so sometimes it is still overlooked by victims and perpetrators.